2022
DOI: 10.1002/cmdc.202200221
|View full text |Cite
|
Sign up to set email alerts
|

SAR Analysis of Heterocyclic Compounds with Monocyclic and Bicyclic Structures as Antifungal Agents

Abstract: Infections caused by eukaryotic organisms, such as fungi, are generally more difficult to treat than bacterial infections. With the widespread use of antifungal drugs in humans and plants, resistance and toxicity have emerged. Therefore, it is desirable to develop new antifungal drugs with low toxicity that are not susceptible to the development of resistance. This review presents a summary of the past few years (2017-2021) of research on heterocyclic compounds as antifungal agents for use in humans and plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…In the current work, we prepared a number of activin receptor-like kinae 5 (ALK5) inhibitors bearing imidazole groups, [39][40][41][42] and found that compounds [43][44][45][46] (7) bearing imidazole and imidazo[2,1-b] [1,3,4]thiadiazole moiety showed a good antifungal activity and high selectivity against Grampositive and Gram-negative bacteria. We hypothesized that the high selectivity of compound 7 may be related to the insertion of a large active group at the 5-position of the imidazo[2,1-b][1,3,4]thiadiazole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, we prepared a number of activin receptor-like kinae 5 (ALK5) inhibitors bearing imidazole groups, [39][40][41][42] and found that compounds [43][44][45][46] (7) bearing imidazole and imidazo[2,1-b] [1,3,4]thiadiazole moiety showed a good antifungal activity and high selectivity against Grampositive and Gram-negative bacteria. We hypothesized that the high selectivity of compound 7 may be related to the insertion of a large active group at the 5-position of the imidazo[2,1-b][1,3,4]thiadiazole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple isomers which differ by the location of the nitrogen atoms and the nature of the ring fusion. The [1,2,4]triazolo [4,3-a]pyridine motif (Figure 1) is found in a variety of biologically active compounds, including antibacterial, antithrombotic, antiinflammatory, antiproliferative, and herbicidal agents [3][4][5][6][7][8]. They can also be used as molecular chemosensors for metal ions, anions, and amino acids [9,10] as well as in the construction of luminophores [11].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from clinical drugs to develop new antifungal drugs is one of the most effective strategies, and there are many reports on structural modifications of fluconazole and ketoconazole . In 2016, Blass et al prepared a series of ketoconazole sulfonamide compounds, which inhibited key enzymes in the cortisol synthesis pathway effectively and served as a potent treatment for metabolic syndrome .…”
mentioning
confidence: 99%
“…Starting from clinical drugs to develop new antifungal drugs is one of the most effective strategies, and there are many reports on structural modifications of fluconazole and ketoconazole. 8 In 2016, Blass et al prepared a series of ketoconazole sulfonamide compounds, which inhibited key enzymes in the cortisol synthesis pathway effectively and served as a potent treatment for metabolic syndrome. 9 In 2020, Starosta and de Almeida reported that ketoconazole− diphenylphosphanomethyl derivatives showed good antifungal activity toward Saccharomyces cerevisiae and C. albicans by inhibiting cytochrome P450 14α-demethylase.…”
mentioning
confidence: 99%